The evolution of marriage in Spain from the francoist dictatorship to the present day - Barreda Marín, Noa; Lumbreras Catalá, María; Martínez Herrero, Alberto (Kortowski Przegląd Prawniczy, 2024)
The aim of this paper is to present a brief summary about the evolution of marriage in Spain: from Catholic marriage during the years of the Francoist dictatorship (1939–1975), going through the democratic transition and the recognition of the right to marriage in the Constitution of 1978, until the necessity for legislative intervention to interpret the constitutional precept more broadly in order to recognise homosexual marriage. Moreover, what has been and continues to be the impact of non-catholic confessions in the Spanish marriage system will be analysed.